-126=-2x-2(4x+13)

Simple and best practice solution for -126=-2x-2(4x+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -126=-2x-2(4x+13) equation:


Simplifying
-126 = -2x + -2(4x + 13)

Reorder the terms:
-126 = -2x + -2(13 + 4x)
-126 = -2x + (13 * -2 + 4x * -2)
-126 = -2x + (-26 + -8x)

Reorder the terms:
-126 = -26 + -2x + -8x

Combine like terms: -2x + -8x = -10x
-126 = -26 + -10x

Solving
-126 = -26 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-126 + 10x = -26 + -10x + 10x

Combine like terms: -10x + 10x = 0
-126 + 10x = -26 + 0
-126 + 10x = -26

Add '126' to each side of the equation.
-126 + 126 + 10x = -26 + 126

Combine like terms: -126 + 126 = 0
0 + 10x = -26 + 126
10x = -26 + 126

Combine like terms: -26 + 126 = 100
10x = 100

Divide each side by '10'.
x = 10

Simplifying
x = 10

See similar equations:

| -8=-3x | | 6x^2+84x+300=0 | | 8x+2x=10x | | 6v+12=4(v-2) | | z+6/3=8 | | 2(3p-6)=5(4-p) | | 8x-2+11x=17 | | 3(2x+4)=9x-3 | | -2.3x+(-1.7x)= | | 38+4z=14 | | a+1+2a+8a= | | 5x^2+70x+155=0 | | -3m^2+14m+5=0 | | 88=4x+4(3x-10) | | 2x+4=x-2 | | 4x^3+17x^2-111x+72=0 | | 0.2z+1.9z= | | 3x+5+8x-2= | | 11q-5+2q-7= | | 10=7-n | | 3x-11=5x+4 | | 3(c-4)=12 | | 56=4x+60 | | x/3-1/2=5.1 | | 12-u=19 | | 5-3x+x=-19+4x | | 2x+4(1-x)=11+5x | | x+0.03x=215 | | 9-8z-3+5z= | | 4+3(i+1)=41+6 | | 8-5x=8+5x | | 8b+7b-4-6b= |

Equations solver categories